2012
DOI: 10.1016/j.clim.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Syk inhibition with fostamatinib leads to transitional B lymphocyte depletion

Abstract: Cell signaling initiated by the B cell receptor is critical to normal development of B lymphocytes, most notably at the transitional B cell stage. Inhibition of this signaling pathway with the syk inhibitor, fostamatinib, has produced significant efficacy in lymphoid malignancies and autoimmune conditions. Here, we demonstrate that short-term use of fostamatinib impairs B lymphocyte development at the transitional stage without affecting mature B cell populations. Additionally, IL-10 producing B cells remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Just how R788 works in vivo is not entirely clear, but in one study where R788 delayed spontaneous diabetes in NOD mice, it also reduced total B-cell numbers and serum immunoglobulin levels while at the same time increasing the numbers of IL-10-producing B cells [106]. Fostamatinib may be more effective at depleting human transitional B cells than mature B cells [107], and thus potentially could be useful for treating autoimmune diseases where RP B cells are a source of autoAb-producing cells.…”
Section: B-cell-associated Therapeutic Targetsmentioning
confidence: 99%
“…Just how R788 works in vivo is not entirely clear, but in one study where R788 delayed spontaneous diabetes in NOD mice, it also reduced total B-cell numbers and serum immunoglobulin levels while at the same time increasing the numbers of IL-10-producing B cells [106]. Fostamatinib may be more effective at depleting human transitional B cells than mature B cells [107], and thus potentially could be useful for treating autoimmune diseases where RP B cells are a source of autoAb-producing cells.…”
Section: B-cell-associated Therapeutic Targetsmentioning
confidence: 99%
“…Outcomes with standard therapy vary because of patient and disease‐related factors . The median age at diagnosis is currently in the near 70s . The proportion of elderly patients with DLBCL appears to be increasing, at least in part because of an increase in the life expectancy of the general population .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The median age at diagnosis is currently in the near 70s. 4 The proportion of elderly patients with DLBCL appears to be increasing, at least in part because of an increase in the life expectancy of the general population. 2 Most clinical trials exclude the very elderly, and the outcomes for these patients vary widely because of heterogeneity in management.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50] Nevertheless, it was recently suggested that CpG PTO induces proliferation of transitional B cells, 51 a B-cell subset expressing polyreactive IgM and sensitive to treatment with syk inhibitors. 52 Albeit the frequency of these cells in freshly isolated peripheral blood B cells from the donors used in this study was very low (0Á1-1%), and blast formation was not observed in the CD27fraction (Fig. 6a), we cannot exclude transitional B cells as the target subpopulation undergoing TLR9-induced receptor revision.…”
Section: Discussionmentioning
confidence: 74%